Women's Participation in Family Economic Improvement through Micro, Small and Medium Enterprises (MSMEs) Banana Peel Crackers - Dinda, Dinda Widi Artanti (Journal of Sumatera Sociological Indicators, 2023)
economy through Micro, Small, and Medium Enterprises (UMKM). The research method used a qualitative descriptive approach. Data was collected through observation, in-depth interviews, literature study, and analysis. The results of the study explain that the role of women has shifted and expanded not only in the reproductive sector but also in the productive, social, and other sectors. Women are involved in all economic activities in households, in which they have a role to contribute to MSMEs. Women who work in UMKM, such as Banana Peel Crackers, can help fulfill their family's economy by increasing family income, meeting family needs, covering children's schooling costs, and saving for other important needs. This participation opens employment opportunities, boosts the economy, and really helps women. Women's participation is one of the drivers for village development by reducing the percentage of the poverty rate. Micro, Small, and Medium Enterprises (UMKM) such as Banana Peel Crackers are included in the category of micro businesses with small capital but significant profits